Massive parallel sequencing unveils homologous recombination deficiency in follicular dendritic cell sarcoma - Lorenzi, Luisa; Haferlach, Torsten; Mori, Luigi; Simbeni, Matteo; Walter, Wencke; Balzarini, Piera; Meggendorfer, Manja; Döring, Claudia; Lonardi, Silvia; Bugatti, Mattia; Agostinelli, Claudio; Mehta, Jay; et al. (Haematologica, 2024)
Standardized treatment options are lacking for patients with unresectable or multifocal follicular dendritic cell sarcoma (FDCS) and disease-related mortality is as high as 20%. Applying whole-genome sequencing (WGS) in one case and whole-exome sequencing (WES) in additional twelve cases, this study adds information on the molecular landscape of FDCS, expanding knowledge on pathobiological mechanisms and identifying novel markers of potential theragnostic significance. Massive parallel sequencing showed high frequency of mutations on oncosuppressor genes, particularly in RB1, CARS and BRCA2 and unveiled alterations on homologous recombination DNA damage repair-related genes in 70% (9/13) of cases. This indicates that patients with high-stage FDCS may be eligible for poly ADP ribose polymerase inhibition protocols. Low tumor mutational burden was confirmed in this study despite common PDL1 expression in FDCS arguing on the efficacy of immune checkpoint inhibitors. CDKN2A deletion, detected by WGS and confirmed by fluorescence in situ hybridization in 41% of cases (9/22) indicates that impairment of cell cycle regulation may sustain oncogenesis in FDCS. Absence of mutations in the RAS/RAF/MAPK pathway and lack of clonal hematopoiesis-related mutations in FDCS sanction its differences from dendritic cell-derived neoplasms of hematopoietic derivation. WGS and WES in FDCS provides additional information on the molecular landscape of this rare tumor, proposing novel candidate genes for innovative therapeutical approaches to improve survival of patients with multifocal disease.
CRIS-Team Scopus Importer:2024-06-14